Catheter-related Blood Stream Infection in a Patient with Hemodialysis - Anti Dharmayanti; Dalima Astrawinata (Acta Medica Indonesiana)
A 31-year-old patient came to visit the outpatient clinic at the hospital for his routine twice-weekly hemodialyis (HD) session. During HD, the patient suddenly developed a fever with shivering. At that time, a diagnosis of catheter-related blood stream infection (CR-BSI) was developed, HD catheter or the catheter double lumen (CDL) was uninstalled and the patient was hospitalized. Results of culture withdrawn through the tip of catheter lumen and peripheral blood revealed identical microorganism, i.e. the Enterobacter cloacae. Diagnosis of CR-BSI in the present case was made based on the 2009 Infectious Disease Society of America (IDSA) criteria. In general, prevention measures for CR-BSI should be taken into account including education for patient, awareness of the health care providers who install the CDL, implementation of procedure for appropriate skin aseptic technique and best practice for HD catheter care, particularly on the exit site of the CDL to prevent the development of CR-BSI.